2022
DOI: 10.3390/jcm11164750
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Chronic Kidney Disease on Mid-Term Outcomes after Revascularisation of Peripheral Arterial Occlusive Disease: Results from a Prospective Cohort Study

Abstract: Objective: The current study aimed to determine the relationship between chronic kidney disease (CKD) and major 12-month outcomes for patients with in-hospital treatment for symptomatic peripheral arterial occlusive disease (PAOD). Methods: An analysis of the prospective longitudinal multicentric cohort study with 12-month follow-up was conducted including patients who underwent endovascular or open surgery for symptomatic PAOD at 35 German vascular centres (initial study protocol: NCT03098290). Severity of CK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Yunir et al ( 2022) demonstrated diabetes mellitus and smoking to be associated with increased mortality in CLTI patients following endovascular revascularization [43]. A recent cohort study by Kotov et al (2022) reported inferior outcomes following arterial revascularization in these patients with concomitant CKD, including a significantly higher risk of mortality, major amputations and MACEs in 1 year [44]. Moreover, the PROMISE II trial identified dialysis as the sole risk factor associated with mortality in CLTI patients undergoing pDVA [10].…”
Section: Discussionmentioning
confidence: 99%
“…Yunir et al ( 2022) demonstrated diabetes mellitus and smoking to be associated with increased mortality in CLTI patients following endovascular revascularization [43]. A recent cohort study by Kotov et al (2022) reported inferior outcomes following arterial revascularization in these patients with concomitant CKD, including a significantly higher risk of mortality, major amputations and MACEs in 1 year [44]. Moreover, the PROMISE II trial identified dialysis as the sole risk factor associated with mortality in CLTI patients undergoing pDVA [10].…”
Section: Discussionmentioning
confidence: 99%